Coarse and fine motion simulator between a magnetically levitated robot and an industrial robot. (18th December 2014) - Tarao, Susumu; Mehrtash, Moein; Tsuda, Naoaki; Khamesee, Mir Behrad
Magnetically levitated robots are widely employed for non-contact manipulation that presents a great promise for using in the various special environments such as in a dust-free room, in a vacuum, in a flammable atmosphere, and in vivo. Meanwhile, they have a disadvantage of small working volume corresponding to the allowable air gap between the levitated object and the electromagnets. In some cases, to construct a combination of a magnetically levitated robot (which can generate a fine motion) and an industrial robot (which can generate a coarse motion and has a comparatively large working envelope) seems an effective way to expand the whole operational working space. On that premise, we are developing an experimental system and simulator for collaborative work between a magnetically levitated robot and an industrial robot. This paper presents the system concept and the configuration of the simulator, and the result of a preliminary simulation experiment which has been performed to evaluate mainly two elements: the numerical magnetically levitated robot model and the numerical industrial robot model.